3-dimensional joint torque calculation of compression sportswear using 3D-CG human model - Matsuda, A.; Tanaka, H.; Aoki, H.; Shimana, T. (Procedia Engineering, 2015)
Recently, there have been many developments in compression sportswear and swimwear. The main purpose of compression sportswear is to keep athletes` muscles warm to prevent muscle strain and fatigue. Now, some compression sportswear has been developed to include a joint protection function. In this study, a design method for joint torque generated by compression sportswear such as competitive swimwear and compression long running tights is proposed. Information on the joint torque generated by sportswear would be useful for compression sportswear design. The proposed method calculates stress-strain relationships of sportswear fabrics using the anisotropic hyperelastic model, and calculates the frictional displacement between the human body and sportswear using a 3D-CG human model. In order to accurately calculate stress, anisotropic material modeling and a stress-softening model were applied to the mechanical characteristics of compression sportswear fabrics. The frictional displacement between the human body and swimwear during swimming was also considered for stress calculations. Typical sportswear fabrics exhibit anisotropic mechanical behavior depending on tensile direction. Also, the stiffness of the fabrics is softened by the maximum strain experienced in each warp and weft fiber. To accurately calculate the joint torques generated by compression sportswear, the anisotropy and stress softening of sportswear fabrics are considered for numerical modeling.